PTU-197 Diagnosis of gastro-esophageal reflux disease (GERD) and prediction of treatment response to proton pump inhibitors (PPI) by prolonged wireless ph monitoring: a prospective assessment. (28th May 2012) - Fox, M; Sweis, R; Tucker, E; Wright, J; Knowles, K; Anggiansah, A; Wong, T; Menne, D
Abstract : Introduction: Increasing duration of pH studies improves consistency of GERD diagnosis but clinical utility of the method is not established. Aim: (1) to identify measurements from prolonged pH studies that discriminate healthy volunteers (HVs) and GERD patients (2) to compare prediction of PPI response from prolonged and standard measurement. Methods: HVs and patients with reflux symptoms entered a prospective trial. Quality of life (RAND-36) and symptom severity (Eraflux) was assessed on and off PPI and after 2 weeks ×2/day PPI. Endoscopy recorded mucosal disease. Wireless pH system (Bravo®, Given Imaging) measured acid reflux and symptoms up to 4 days. Receiver Operating Curve (ROC) assessed prediction of PPI response. For each prediction 80% of patients were randomly selected as training set, remaining 20% constituted test set. This was repeated 200 times producing average ROC with SEs. Area under Curve (AUC) quantified quality of prediction. Results: Complete data were available from 25/33 HVs (18F, age 20–56) and 70/108 patients (31F, age 18–77), >320 days in total. Oesophagitis was present in 9 HVs (32%: Grade A) and 26 patients (33%: Grade A=19, B=2, C-D=5). Acid exposure time was elevated (AET >5.6%) in 3 (12%) HVs and 35 (50%) patients. Eraflux off-PPI was >25 (consistent with GERD) in 60/63 patients and fell by mean 7 (95% CI 5 to 10) on PPI, 46% reported positive response (>3 fall). Diagnosis: Endoscopy, AET and reflux-symptom association analysis (Symptom Index (SI)) did not discriminate health/disease; but reflux-associated symptoms/day (nRS/Day) covered different ranges for HV and patients. Logistic regression with bootstrap validation identified that ≥3 RS/day corresponded to ∼50% probability that participant was a patient. PPI response: Clinical parameters and AET did not predict outcome. SI (9.2 vs 30.2, p=0.0023) and nRS/Day (1 vs 2.6, p=0.012) were higher in responders. RAND-36 scores for poor physical role and pain were higher in non-responders (p∼0.1). SI ROC had an AUC of 0.73 (CI 0.51 to 0.92). SI >25 was the optimal cut-off for identifying PPI responders (Abstract PTU-197 figure 1 ). Prediction quality from 24 h studies was lower (AUC 0.69) and CIs for all parameters were wider with lower CI. Conclusion: Diagnostic consistency for all parameters increases with study duration. A simple count of nRS/Day best discriminates HVs from patients on pH studies. SI >25 provides single best prediction of PPI response; but quality of predictions was modest in this population with low PPI response. Competing interests: None declared.